SOLVENCY OF LOCAL GOVERNMENT BUDGETS IN THE SOUTHERN SUMATRA REGION FOR THE 2020-2023 FISCAL YEARS - Juminten Wulandari; Robinson Robinson (Journal of Research in Social Science and Humanities, 2025)
This study aims to analyze the solvency of local government budgets in the southern Sumatra region. The method used is quantitative with a descriptive approach. Secondary data were obtained from the budget implementation reports of local governments in the Sumbagsel region for the 2020-2023 fiscal years. The population in this study consisted of 65 local governments in the Sumbagsel region. Sampling was conducted using a saturated sampling technique, where all members of the population were included as samples in the study. The results of the study indicate that in the Sumbagsel region from 2020 to 2023, the average budget solvency index (0.44) exceeded the financial health indicator, meaning that local governments in Sumbagsel were able to meet their budget obligations and cover expenditures from existing revenues. Budget solvency was classified as adequate and reflected sound financial management. At the district level, the average budget solvency index for Cluster 1 (0.43), Cluster 2 (0.46), and Cluster 3 (0.53) all indicate healthy financial conditions, signifying greater capacity for local governments to fund operational expenditures. Cluster 3 has the highest solvency and budget flexibility. At the city government level, there are two clusters with average budget solvency indices of 0.31 for Cluster 1 and 0.36 for Cluster 2. Both clusters have exceeded the minimum financial health threshold of 0.142, but Cluster 2 has better and more stable financial conditions than Cluster 1. A comparative analysis based on clusters in districts/cities shows good budget solvency. However, Cluster 1 in cities has the lowest budget solvency level.